2019
DOI: 10.3390/beverages5010011
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Chlorogenic Acids through Coffee and Health Implications

Abstract: Chlorogenic acids (CGA) are the main antioxidant compounds in the Western diet, due to their high concentrations in coffee associated with the high consumption of the beverage. Until about 10 years ago, like many other phenolic compounds, CGA were thought to be poorly absorbed in the human digestive system. Along the years, large amounts of information on the absorption and metabolism of these compounds have been unveiled, and today, it is known that, on average, about one third of the consumed CGA from coffee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 232 publications
(334 reference statements)
2
89
0
2
Order By: Relevance
“…In addition to forming complexes with chlorogenic acids, according to the authors, about 10% of caffeine could be bound to other types of substances, such as proteins and, after roasting, to melanoidins. For structures and other information on chlorogenic acids, please see reference [103].…”
Section: Caffeine Complexation With Chlorogenic Acidsmentioning
confidence: 99%
“…In addition to forming complexes with chlorogenic acids, according to the authors, about 10% of caffeine could be bound to other types of substances, such as proteins and, after roasting, to melanoidins. For structures and other information on chlorogenic acids, please see reference [103].…”
Section: Caffeine Complexation With Chlorogenic Acidsmentioning
confidence: 99%
“…Interestingly, 3-caffeoylquinic acid (CQA) also known as chlorogenic acid was previously shown to chelate iron (Fe 3+) in a ratio of 3/1 (chlorogenic acid/iron) in vitro at pH 7.4 [ 29 ]. Moreover, it has been reported that the antioxidant effect of CQA is attributed to the chelate structure with iron [ 29 , 30 ]. Thus, our data suggest that 3,5-dicaffeoylquinic acid (di-CQA) as being a derivative of 3-caffeoylquinic acid might also sequester iron, limiting thus the Fe 3+ availability, which in turn would result in increased pyoverdine siderophore production by P. aeruginosa.…”
Section: Resultsmentioning
confidence: 99%
“…An overview of studies discussing coffee/caffeine intake with cognitive impairment and their results are shown in Table 2. AD is the most common cause of dementia [37]. Several studies have suggested that coffee is associated with reduced risks of developing AD [16].…”
Section: Review Bioactive Compounds Of Coffee and Their Propertiesmentioning
confidence: 99%
“…Several studies have suggested that coffee is associated with reduced risks of developing AD [16]. This could be due to the effects of caffeine and CGAs on the adenosine receptors that ultimately play a role in preventing toxic β-amyloid peptide deposits in the brain [37]. This mechanism can be very specific to the extent and type of adenosine receptors involved because animal models with AD observed the neuroprotective potential of caffeine due to its action on A2AR rather than A1 receptors [38].…”
Section: Review Bioactive Compounds Of Coffee and Their Propertiesmentioning
confidence: 99%